A Microfiltration Polymer‐Based Hollow‐Fiber Cathode as a Promising Advanced Material for Simultaneous Recovery of Energy and Water. Issue 43 (12th September 2016) - Katuri, Krishna P.; Bettahalli, Narasimha Murthy Srivatsa; Wang, Xianbin; Matar, Gerald; Chisca, Stefan; Nunes, Suzana Pereira; Saikaly, Pascal Elias
Abstract : A novel electrocatalytic and microfiltration polymeric hollow fiber is fabricated for simultaneous recovery of energy (H2 ) and clean fresh water from wastewater, hence addressing two grand challenges facing society in the current century (i.e., providing adequate supplies of clean fresh water and energy as the world's population increases).